Fly-in-fly-out work: A review of the impact of an extreme form of work-related travel on mental health - Fruhen, Laura; Gilbert, Jess; Parker, Sharon (SAGE PUBLICATIONS INC, 2023)
Fly-in-fly-out work represents a specific and extreme case of work-related travel in which workers are housed by employers and have fixed schedules that prescribe blocks of time at work followed by blocks of time at home, alongside other rules. This paper provides an overview of the literature regarding the mental health implications of FIFO work. Moreover, an integrative model of FIFO work is proposed that brings together its key defining attributes: the simultaneous fracturing and blending of personal and work lives, which FIFO workers, and by extension other work-related travellers, experience. The model identifies the key attributes of this type of work arrangement that shape fracturing namely the commute (i.e., duration, mode, distance) and rosters (i.e., length and ratio of time on and off) and blending experiences, namely accommodation (i.e., type and quality), extent to which autonomy is limited (i.e., via choice in food, activities, scheduling) and social isolation. While developed for an extreme, highly standardized, and specific case of work-related travel, the model may also be useful in research focused on work related travel more broadly,